The Process of Learning Arabic Calligraphy at the Guidance Institute in the Aberawan Area - Hamid, Muhammad Abdul; Aisyah, Devy (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The purpose of this research is descriptive about how to learn Arabic calligraphy at the Tutoring Institute in the area, descriptive about how to train students' Arabic calligraphy skills at the Tutoring Institute in the Aberawan area. The type of research used by researchers is descriptive qualitative research. Data sources include calligraphy instructors, calligraphy teachers, some students at Al-Irshad Islamic Boarding School, and other data sources. Data collection techniques include observation interviews and documentation. Data analysis used is data selection, data collection, content analysis, and conclusion drawing. The researcher concluded from the research conducted by the researcher that the Arabic activities of the Islamic boarding school are very good and have a positive impact on the achievement of students, because it is seen from several elements, namely: learning methods, and the ability of students to write Arabic.